Analysis of the Plugged-in Method Through Wordwall in Teaching Procedure Text Writing at the Elementary Level - Adelia Ananda Aviva; Innany Mukhlishina (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
This study aims to analyze the application of the plugged-in method through Wordwall in teaching procedure text writing to Grade V students at SDN Kemuning. This study employs a descriptive qualitative approach involving 20 Grade V students, using observation, interviews, and documentation analysis. The findings demonstrate that interactive activities, such as match-up exercises, help students understand the sequence of steps more coherently through immediate system feedback. The use of Wordwall also increases student enthusiasm because the learning process becomes more varied and aligned with digital technology. Teachers play an important role in guiding the use of digital media, maintaining structured learning activities, and providing assistance when technical problems arise, such as login difficulties or unstable internet connections. Overall, the findings indicate that Wordwall's plugged-in method can create a more engaging learning environment while improving students' ability to compose procedure texts systematically. Wordwall can therefore be utilized as an effective digital learning medium to enhance the accuracy of procedural text structure at the elementary level and to contribute to the development of digital-based writing instruction strategies.